2008
DOI: 10.2478/v10042-008-0029-0
|View full text |Cite
|
Sign up to set email alerts
|

Plasminogen activator inhibitor-1 (PAI-1) and urokinase plasminogen activator (uPA) in sputum of allergic asthma patients.

Abstract: Urokinase plasminogen activator (uPA) and its inhibitor (PAI-1) have been associated with asthma. The aim of this study was to evaluate concentration of uPA and PAI-1 in induced sputum of house dust mite allergic asthmatics (HDMAAs). The study was performed on 19 HDM-AAs and 8 healthy nonatopic controls (HCs). Concentration of uPA and PAI-1 was evaluated in induced sputum supernatants using ELISA method. In HDM-AAs the median sputum concentration of uPA (128 pg/ml; 95% CI 99 to 183 pg/ml) and PAI-1 (4063 pg/ml… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 21 publications
1
16
0
Order By: Relevance
“…This study supports previous observations linking the plasmin system with pathogenesis of allergic asthma [8][9][10][11][12][13][14][15][16]. In the present study we demonstrate that, in the airways of allergic asthma patients, allergen exposure leads to up-regulation of both components of the plasmin system: PAI-1 and uPA.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…This study supports previous observations linking the plasmin system with pathogenesis of allergic asthma [8][9][10][11][12][13][14][15][16]. In the present study we demonstrate that, in the airways of allergic asthma patients, allergen exposure leads to up-regulation of both components of the plasmin system: PAI-1 and uPA.…”
Section: Discussionsupporting
confidence: 93%
“…Sputum induction. Sputum was induced as described before [16]. Briefly, after premedication with 200 mcg of salbutamol patients inhaled hypertonic saline solution (3 to 5% NaCl).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, recent studies showed that asthmatic subjects have increased concentrations of nonkinase plasminogen activator and plasminogen activator inhibitor [23] compared to controls and Neurokinin A significantly raises during exacerbations [24]. Interleukin-8 (IL-8) is a neutrophil chemoattractant which has been shown to be increased during asthma exacerbations [25] and in patients with severe persistent asthma [17], suggesting a role for monitoring asthma exacerbations and assessing the effectiveness of a medication in severe asthmatics.…”
Section: Fluid-phase Mediatorsmentioning
confidence: 99%